Role of HR and the entire organization in talent management in the upcoming 4th Industrial Revolution - Sudarsanan, Samay (2020)
The Fourth Industrial Revolution depicts the accelerated alterations as to how we live, work, and relate to each other due to the implementation of computer network-physical systems, the Artificial intelligence, and IoT. In our manufacturing plants and places of work, as we incorporate smart innovations, networked systems interact, conceptualize the entire production chain, and make independent decisions. It is anticipated that such a revolution will influence all professions, sectors, and markets. Even as this is in some ways an expansion of the 3rd Industrial Revolution (Digital Revolution) technology and automation due to speed, scope and system impact of the fourth revolution changes, it is considered the new and next age. With skill replacement by Artificial Intelligence being inevitable, role of Human Resource (HR) has become more challenging and crucial. With higher competition, human workforce is locking horns with technology and system to stay ahead in the race. The expectations of organisations are ever rising with cost reduction and increased productivity, HR has been the linking bridge between organisations and manpower. The outcome of this report is to understand the impact 4th Industrial Revolution has on the workforce, how HR has developed different procedures and process to attract new talent and retain existing talent. The methodologies HR has to undertake to develop knowledge and skills of the current talent are also explained in this report.